Research progress of migrasomes: from genesis to formation, physiology to pathology - Tang, Hua; Huang, Zhe; Wang, Ming; Luan, Xingzhao; Deng, Zengfu; Xu, Jian; Fan, Wei; He, Dongsheng; Zhou, Chong; Wang, Liangbin; Li, Jun; Zeng, Fanfeng; et al. (Frontiers in Cell and Developmental Biology, 2024)
Migrasomes are recently identified organelles that form at the ends or forks of retraction fibers (RFs) behind migrating cells and are expelled from the cell through cell migration. Migrasomes contain signaling molecules which are captured by surrounding cells along with migrasomes or released into the extracellular environment following the rupture of the migrasomes. Finally, through the action of these signaling molecules, migrasomes facilitate the entire process of information conveyance. In addition, migrasomes also serves as a "scavenger" by removing damaged mitochondria from the cell to ensure cellular viability. Thus, migrasomes play a pivotal role in the integration of temporal, spatial, specific chemical information and the clearance of cellular harmful substances, critical for grasping migrasomes' functions. This review delves into the latest advancements in migrasomes research, covering aspects such as migrasomes' discovery, distribution, structure and characteristics, genesis and regulation mechanisms, and their correlation with diseases. Additionally, we scrutinize the present investigational findings on migrasomes within the cancer domain, examining their potential impact on cancer and prospective research avenues.